The imperative of physics-based modeling and inverse theory in computational science - Willcox, Karen E.; Ghattas, Omar; Heimbach, Patrick (Nature Computational Science, 2021)
To best learn from data about large-scale complex systems, physics-based models representing the laws of nature must be integrated into the learning process. Inverse theory provides a crucial perspective for addressing the challenges of ill-posedness, uncertainty, nonlinearity and under-sampling.